Canoes, Modernity, and the Colonial Imagining of Progress. Issue 2 (3rd July 2018) - Ritts, Max; Johnson, Kelsey; Peyton, Jonathan
Abstract : This article, part photo-essay and part treatise, explores the interplays of history, photographic representation, and archival circulation at work in colonial imaginings of coastal canoes. Inspired by the work of Walter Benjamin, we analyze the archival photographic record in British Columbia to challenge narratives of progress; instead, we insist that Benjamin's notion of the "optical unconscious" provides a method for reading canoe photos against broader logics of representation and colonial modernity. Our empirical reading of the colonial archives produces a circumscribed account of the representation of the canoe as a persistent technology of Indigenous mobility, labor, and lifeways, but also as a technology, the "disappearance" of which was used to assert narratives of decline and colonial progress. We conclude by suggesting that this article could be read as part of an emerging convergence of critical visual methods within both human geographies of the sea and mobility studies. In this sense, we suggest that the photography-based methods taken here hold potential for growing geographical engagements in marine mobility studies.